Quantifying Antimicrobial Use in Dutch Companion Animals - Hopman, Nonke E. M.; van Dijk, Marloes A. M.; Broens, Els M.; Wagenaar, Jaap A.; Heederik, Dick J. J.; van Geijlswijk, Ingeborg M. (Frontiers in Veterinary Science, 2019)
Antimicrobial resistance is an increasing threat, both in human and in veterinary medicine. To reduce the selection and spread of antimicrobial resistance, antimicrobial use should be optimized, also in companion animals. To be able to optimize antimicrobial use, a feasible method to quantify antimicrobial use and information on current antimicrobial use are needed. Therefore, a method to quantify antimicrobial use was developed, using the number of Defined Daily Doses Animal (DDDA). This method was used to explore applied antimicrobial classes and to identify differences in prescribing patterns in time and between veterinary clinics. Antimicrobial procurement data of the years 2012-2014 were collected retrospectively from 100 Dutch veterinary clinics providing care for companion animals. The mean number of DDDAs per clinic per year decreased significantly from 2012 to 2014. A shift in used classes of antimicrobials was seen as well, with a significant decrease in use of third choice antimicrobials (i.e. fluoroquinolones and third generation cephalosporins). Large differences in total antimicrobial use were seen between clinics ranging from 64-fold in 2012 to 20-fold in 2014. Despite the relative low and decreasing antimicrobial use in Dutch companion animal clinics during the study, the substantial differences in antimicrobial prescribing practices between clinics suggest that there is still room for quantitative and qualitative optimization of antimicrobial use.